2014
DOI: 10.1111/j.1532-950x.2014.12170.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Growth Factor Treatments on the Fibrochondrogenic Potential of Canine Fibroblast‐Like Synoviocytes for Meniscal Tissue Engineering

Abstract: Objective: To determine the in vitro effects of differing growth factor treatments on the fibrochondrogenic potential of fibroblast-like synoviocytes from cruciate ligament deficient femorotibial joints of dogs. Study Design: In vitro study. Sample Population: Synoviocytes from dogs (n ¼ 8) with naturally occurring cruciate ligament insufficiency. Methods: Synoviocytes were cultured in monolayer and synthesized into tensioned synoviocyte bioscaffolds (TSB) suspended in media containing TGF-b3, or FGF-2, TGF-b1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…Aggrecan within joint tissues is produced by chondrocytes [25] and fibroblast-like synoviocytes [26]. Although IGF1 is thought to be the major stimulator of aggrecan synthesis by articular cartilage cells [27] we did not demonstrate this effect of IGF1 used at the concentration observed in cartilage interstitial fluid [10].…”
Section: Discussionmentioning
confidence: 58%
“…Aggrecan within joint tissues is produced by chondrocytes [25] and fibroblast-like synoviocytes [26]. Although IGF1 is thought to be the major stimulator of aggrecan synthesis by articular cartilage cells [27] we did not demonstrate this effect of IGF1 used at the concentration observed in cartilage interstitial fluid [10].…”
Section: Discussionmentioning
confidence: 58%
“…Despite the poor chondrogenic capacity of canine MSCs, so far, only a few studies have investigated the effect of growth factors on canine MSC chondrogenesis [30, 41]. Russel et al observed no evidence of cartilage matrix deposition in canine adipose tissue-derived MSCs, even when BMP-2 was added to chondrogenic induction medium containing TGF-β3 [30].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several attempts have been made to regenerate fibrocartilaginous tissue with tissue engineering approaches [ 32 34 ]. Most of these studies emphasize on the optimization of scaffolds or growth factors used for fibrocartilage engineering.…”
Section: Discussionmentioning
confidence: 99%